Analisis Struktur, Perilaku, Dan Kinerja Industri Popok Bayi Sekali Pakai Di Indonesia - Lulu Sugiarto (Universitas Tarumanagara, 2019)
The purpose of this research is to is to determine how is the structure, conduct, and performance of baby diaper industry in Indonesia. The paradigm known as Structure - Conduct - Performance (SCP) shown those three aspects are integrally related.The type of data at this research is secondary data which is collection from Badan Pusat Statistik (BPS), annual report of baby diaper industry published by Nielsen from 2012 to 2016 and literature related to this study. The research methodology applies descriptive analytical method in describing SCP of baby diaper industry in Indonesia systematically and accurately. The analysis on structure refer to elucidation on products, industry concentration ratio (CR), Herfindahl-Hirschman Index (HHI), technology, demands and market condition and ease of entry and exit (Porter Five Forces Model). The conduct analysis refer to pricing, product, distribution and promotion strategies. The performance analysis refers to industrial growth and corporate social responsibility (CSR). The result shows that the market structure is quite stable. CR4 calculation indicating oligopoly market. HHI calculation is over 2.500 representing highly concentrated exposed to high technology. Five Porter Forces showed fives strength analysis from threat of entry, power of suppliers, power of buyers, threat of substitutes and rivalry among existing competitor. Price determination, product development, strengthen distribution line, and aggressive advertising and promotion are part of the strategies. Moreover, there is high tendency of merger and supported by managerial implication. From financial perspective, mamy poko remains on top.